Studies on the alleviating effect of Bifidobacterium lactis V9 on dextran sodium sulfate-induced colitis in mice - Duan, Xiaoyan; Wu, Rilige; Li, Jianbo; Li, Zeya; Liu, Yanqi; Chen, Ping; Wang, Bangmao (Frontiers in Medicine, 2025)
BackgroundInflammatory bowel disease (IBD) has become a global public health problem with complex pathogenesis and limited therapeutic options. We aimed to investigate the potential mechanisms by which Bifidobacterium lactis V9 (V9) alleviated colitis in a dextran sodium sulfate-induced colitis model mice.MethodsMice were induced to develop colitis by drinking DSS solution to induce colitis. The expression of the relevant factors in the blood supernatant of the mice was determined by ELISA. RT-qPCR and Western blotting were used to detect mRNA and protein expression of target genes. The fecal microbiota was analyzed by 16S rRNA sequencing. Intestinal metabolites were analyzed by untargeted metabolomics;ResultsV9 effectively improved the overall symptoms of the colitis model mice. H&E showed that V9 re-stored the intestinal tissue structure. ELISA showed that V9 decreased the levels of IL-6, IL-22, and TNF-α and increased IL-10, SP, VIP, and 5-HT. V9 increased the expression of AHR, CYP1A1, MUC2, Claudin-3, Occludin, and ZO-1, and decreased 5-hydroxytryptamine transporter and Claudin-2. V9 increased the abundance of gut microbiota in colitis mice to promote the growth of beneficial bacteria. V9 increased tryptophan metabolites, and short-chain fatty acids, and improved gut inflammation.ConclusionV9 attenuates intestinal inflammation, improves the mucosal barrier, modulates intestinal microecology and exerts a protective effect in a mouse model of DSS-induced colitis.